Analysis of Acceptable Tax Avoidance in Good Business Purpose at Indonesia - Harinurdin, E (KnE Social Sciences, 2018)
The loss of the boundaries of a country in free trade and globalization promotes the flow of goods and services to be increased. It is also a result of the current financial integration. In addition to the factors of labor, natural resources, bureaucracy, tax issues also become one of the considerations for investors to invest. Many companies in the world do tax planning in order to minimize their tax liabilities. The Government of Indonesia, as one investment destination of foreign investment, should have a policy of anti-tax avoidance. This was done in addition to providing justice for all businesses and also providing legal certainty in order to enforce tax obligations. The anti-tax avoidance policies will shut down and deter the opportunities for aggressive tax avoidance. This study was conducted to discuss the anti-tax avoidance policies in good business practice in Indonesia. Referring to the theoretical perspectives, research paradigms are used, and the nature of this research is descriptive with qualitative analysis. The performance of the company in the context of acceptable tax planning that is transfer pricing, tax haven country utilization, thin capitalization, treaty shopping and Controlled Foreign Corporation. Efforts should be done by the government in addition to the importance of checks and improvement of regulations and making them effective in order to counteract tax avoidance practices and exchange of information on domestic and international level. Keywords: investment, tax, tax avoidance